Integrated Resource-Based View and Dynamic Capabilities for SME internationalization: Early Evidence from Indonesian Export-Ready Firms - Mirza Esvianti; Sudarmiatin Sudarmiatin; Heri Pratikto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study explores how the integrated Resource-Based View (iRBV) and Dynamic Capabilities (DC) explain the early stage of SME internationalization in Indonesia. An exploratory single-case study design is employed on a koi-breeding SME that has engaged in export activities, using a Likert-scale questionnaire to identify VRIN resources, dynamic capabilities, export performance, and internationalization barriers. The findings indicate that the SME possesses relatively strong export market knowledge, network competence, and quality reputation, but remains weak in global certifications, administrative support, and logistical capacity. From a DC perspective, sensing and seizing capabilities are already developed, whereas transforming capability is still limited in terms of reconfiguring the business model, strengthening human resources, and institutionalizing export routines. Overall, the results underscore that the success of SME internationalization is determined not only by the ownership of internal resources, but also by the firm’s ability to reconfigure those resources in the presence of environmental and institutional constraint.